Factors that influence consumer purchasing behavior using guerrilla marketing approach / Abu Izzat Jalaluddin - Jalaluddin, Abu Izzat (Faculty of Business and Management, 2014)
This study is conducted as a partial fulfillment of the coursework of Final Semester Project Paper. The title of the study is factors that influence consumer purchasing behavior using guerrilla marketing approach. The modern era has made each consumer experience a newer concept of marketing communication in his continuing ask for satisfying needs and wants, therefore guerrilla marketing must be implement in the best way.. The main objectives of study are to identify the relationship between creativity, humorous, differentiation and value proposition toward consumer purchasing behavior. The other objective is to determine the rank of element and the most influencing factor that influence consumer purchasing behavior. The result from the study show that the most influencing factor that affect the consumer purchasing behavior. It also indicated that the rank of differentiation element in guerrilla marketing approach that influences the consumer purchasing behavior is high. And also it indicates that independent variables which is creativity, humorous, differentiation, and value proposition are significantly and positively related to the consumer purchasing behavior.